A Brightness Amplifier on Manganese Atom Transitions with a Pulse Repetition Frequency of up to 100 kHz; Technical Physics Letters; Vol. 44, iss. 12 - Trigub M. V. Maksim Viktorovich; Shiyanov D. V. Dmitry Valeryevich; Sukhanov V. B. Viktor Borisovich; Petukhov T. D, Timofey Dmitrievich; Evtushenko G. S. Gennady Sergeevich (2018, 2018)
Title screen